2018
DOI: 10.33866/phytopathol.030.02.0461
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF SEED DRESSING CHEMICALS ON EMERGENCE, YIELD AND AGAINST SOIL & SEED BORN DISEASES OF WHEAT

Abstract: Field studies were carried out at Adaptive Research Farm, Sheikhupura Punjab, Pakistan having rice- wheat cropping system to evaluate the efficacy of three different fungicides against seed or soil borne wheat diseases (Root rot, Loose smut & Black Point disease) during two successive seasons 2015-16 & 2016-17.The fungicides were Thiophenate methyl, compound fungicides i.e. Tubeconzol+ imidachloprid and Difenoconazol + cypnoconazol used as seed treatment at the rate of 2.5 g , 4 ml & 1 ml per kg of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…A study in Pakistan revealed that tebuconazole + imidacloprid and difenoconazole + cyproconazole were the most effective chemicals for the management of black point disease of wheat ( Shahbaz et al., 2018 ). Triazole fungicides (e.g., propiconazole and tebuconazole) inhibit the synthesis of sterols, which are building blocks of the membranes of fungal cells.…”
Section: Black Pointmentioning
confidence: 99%
“…A study in Pakistan revealed that tebuconazole + imidacloprid and difenoconazole + cyproconazole were the most effective chemicals for the management of black point disease of wheat ( Shahbaz et al., 2018 ). Triazole fungicides (e.g., propiconazole and tebuconazole) inhibit the synthesis of sterols, which are building blocks of the membranes of fungal cells.…”
Section: Black Pointmentioning
confidence: 99%
“…Biocontrol agents, together with methyl jasmonate or salicylate, were also found to be effective in controlling this disease [43,44]. Management of black point in seeds can be achieved through the use of resistant varieties, fungicides (tebuconazole, imidacloprid, difenoconazole, and cyproconazole), or biocontrol agents [45]. The limitations of all these methods are the same as for the treatment of all fungal infections mentioned above.…”
Section: Introductionmentioning
confidence: 99%